Frequency and Site of Skeletal Metastatic Lesion Detected by Bone Scintigraphy in Newly Diagnosed Asymptomatic Cancer Patients (Bangladesh Journal of Nuclear Medicine, 2018)
Objectives: Bone is one of the most common organ for metastasis. Bone scintigraphy is widely used for staging of cancer patients before initiation of chemotherapy and adjuvant therapy and it can detect both symptomatic and asymptomatic bone metastases. The purpose of this study was to determine the frequency and site of metastatic bone lesion detected by bone scintigraphy in newly diagnosed asymptomatic cancer patients who werwe referred to National Institute of Nuclear Medicine & Allied Sciences (NINMAS) for bone scintigraphy.Patients and Methods: This cross sectional observational type of study was carried out in NINMAS from July 2015 to June 2016. A total of 116 newly diagnosed asymptomatic cancer patients referred for the first time bone scintigraphy were included in this study.Results: Of the total 116 patients (57 male and 59 female; mean age: 54.8 ± 14.0 years), 46 (39.7%) patients had carcinoma breast, 30 (25.9%) patients had carcinoma prostate, 12(10.3%) patients had carcinoma lung, 8(6.9%) patients had carcinoma urinary bladder, 4(3.4%) patients had renal cell carcinoma and 16(13.8%) patients had other cancer. Bone scan was found positive for metastatic disease in 44.8% patients. Most common sites of bone metastases in different types of cancer in newly diagnosed asymptomatic cancer patients were rib, then hip bone, vertebral column (lumbar vertebra, thoracic vertebra respectively), sternum and skull.Conclusion: In this study, it was revealed that newly diagnosed asymptomatic cancer patients are frequently associated with metastatic bone disease, those can be detected by bone scintigraphy.Bangladesh J. Nuclear Med. 20(1): 14-18, January 2017